Direct transfer of micro-molded electrodes for enhanced mass transport and water management in PEMFC - Deshmukh, Ashvini B.; Kale, Vinayak S.; Dhavale, Vishal M.; Sreekumar, K.; Vijayamohanan, K.; Shelke, Manjusha V. (Electrochemistry Communications, 2010)
Soft lithography technique is used to micropattern the electrodes on the electrolyte membrane of polymer electrolyte fuel cell (PEMFC) in order to alleviate the issues due to poor water management and inadequate reactant distribution in the fuel cell environment. Membrane electrode assembly with the micropatterned electrode has shown an increase in power density at a higher temperature as well as at a higher relative humidity when compared to a flat electrode. Consistency in cell performance is observed in the case of micropatterned electrodes. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Bipolar plate-less PEM fuel cell; Micropatterned electrodes; Microtransfer molding; Soft lithography

High efficiency electron field emission from protruded graphene oxide nanosheets supported on sharp silicon nanowires - Devarapalli, Rami Reddy; Kashid, Ranjit V.; Deshmukh, Ashvini B.; Sharma, Ponchami; Das, Manash R.; More, Mahendra A.; Shelke, Manjusha V. (Journal of Materials Chemistry C, 2013)
Graphene oxide (GO) potentially has applications in vacuum microelectronic devices for realization of field emission displays. Graphene and its derivatives are expected to be efficient field emitters due to their unique electrical properties. However, the flat sheet structure of graphene or GO allows electron field emission only from the edges of graphene and GO nanosheets. In order to extract maximum field emission current density at lower applied voltage from the GO nanosheets, we supported and stretched them on sharp tips of silicon nanowires (SiNWs). Highly efficient and stable field emission with low turn-on field was observed for these SiNW-GO heterostructures. The sharp protrusions created by stretching of the GO nanosheets on SiNWs locally enhance the electric field and thus enhance the field emission characteristics. The dominant use of silicon in electronic devices makes this approach robust for the development of field emission devices using graphene based field emitters.

Synthesis and electrochemical performance of a single walled carbon nanohorn-Fe3O4 nanocomposite supercapacitor electrode - Deshmukh, Ashvini B.; Shelke, Manjusha V. (RSC Advances, 2013)
A new Fe3O4-SWCNH nanocomposite was synthesized as an electrode material for supercapacitors. The nanocomposite exhibited a high specific capacitance of 377 F g(-1) and delivered a stable discharge capacitance at a current density of 1 A g(-1) over 1000 cycles between 0 and 1.2 V.

Functional silicon nanostructures derived from drying-mediated self-assembly of gold nanoparticles - Deshmukh, Ashvini B.; Devarapalli, Rami Reddy; Shelke, Manjusha V. (Journal of Nanoparticle Research, 2014)
Self-assembly of nanoparticles is an efficient technique where nanobuilding blocks spontaneously organize into ordered structures by thermodynamic and other constraints. We demonstrate that multifunctional Silicon (Si) nanostructures with unique morphologies like sheets, plates and flakes can be etched chemically by taking an advantage of natural self-assembly of gold nanoparticles (AuNPs) characterized with drying kinetics under external stimuli. We further demonstrated antireflection properties of the as-synthesized Si nanostructures.
Keywords: Antireflective material; gold nanoparticles; Metal-assisted chemical etching; Self-assembly; Si Nanostructures

Plasmon-enhanced photocurrent generation from click-chemically modified graphene - Yenchalwar, Sandeep G.; Devarapalli, Rami Reddy; Deshmukh, Ashvini B.; Shelke, Manjusha V. (Chemistry-A European Journal, 2014)
The visible-light response of Au nanoparticles (AuNPs) assembled on rGO through different molecular bridges was investigated by transient photocurrent generation. We prepared rGO with two self-assembled monolayers (SAMs), one linear and the other with aromatic triazoles through a click cycloaddition reaction. A fivefold photocurrent enhancement was observed for triazole linkers over the aminopropyltrimethoxysilane (APTMS) linker. Cyclic voltammetry (CV) and impedance measurements also suggest fast electron transfer on account of the low resistance offered by the click-modified rGO surface whereby introduction of triazoles offers the efficient bridge between the donor AuNPs and acceptor rGO.
Keywords: Gold; graphene; Nanoparticles; photophysics; surface plasmon resonance

Synthesis and electrochemical performance of a single walled carbon nanohorn-Fe3O4 nanocomposite supercapacitor electrode (vol 3, pg 21390, 2013) - Deshmukh, Ashvini B.; Shelke, Manjusha V. (RSC Advances, 2014)

Electrochemical capacitive energy storage in PolyHIPE derived nitrogen enriched hierarchical porous carbon nanosheets - Deshmukh, Ashvini B.; Nalawade, Archana C.; Karbhal, Indrapal; Qureshi, Mohammed Shadbar; Shelke, Manjusha V. (Carbon, 2018)
Porous and interconnected electrodes based on carbon nanoarchitectures offer comprehensive advantages of large specific surface area and high porosity consequently increasing the specific capacitance of ultracapacitor energy storage systems. Emulsion-templated polymers, PolyHIPEs (Polymerized High Internal Phase Emulsions) are highly porous polymers with a structure of cages interconnected by windows thus provide suitable framework to create such porous carbon nanostructures. Herein, nitrogen enriched porous carbon nanosheets are synthesized by pyrolysis of polymer-silica hybrid PolyHIPE and subsequent silica removal. This nitrogen enriched porous carbon nanosheets when tested as an electrode for ultracapacitor, showed specific capacitance as high as 209 F/g at a current density of 1 A/g in 1 M H2SO4 with excellent capacity retention over long cycling. (c) 2017 Elsevier Ltd. All rights reserved.
Keywords: Energy storage; Nitrogen enriched porous carbon nanosheets; PolyHIPE template; Ultracapacitor

Highly durable Li-ion battery anode from Fe3O4 nanoparticles embedded in nitrogen-doped porous carbon with improved rate capabilities - Deshmukh, Ashvini B.; Dwivedi, Pravin K.; Nalawade, Archana C.; Qureshi, Mohammed S.; Shelke, Manjusha V. (Journal of Materials Science, 2020)
For next generation, lithium-ion batteries (LIBs) developing high capacity anode materials are crucial with increasing demand of large-scale application. Conversion-type anode materials are promising if stable cycling behavior could be achieved. In this work, a nitrogen-doped porous carbon-Fe3O4(NPC-Fe3O4) nanocomposite is synthesized via a simple and scalable approach. Composite is prepared by pyrolysis of polymer silica hybrid PolyHIPE (high internal phase emulsion) into NPC, and Fe3O4 nanoparticles (NPs) are anchored on its surface via hydrothermal synthesis. As-prepared NPC-Fe3O4 nanocomposite delivers high reversible capacity of around 1001 mAhg(-1)at 0.1 Ag-1 current density and rate capabilities and displays excellent cycling stability as high as 95% capacity retention even after 400 cycles. Superior electrochemical performance of NPC-Fe3O4 is attributed to the hierarchical porous structure and nitrogen doping of carbon which shorten the diffusion path of Li+ and provide ample space to prevent aggregation of Fe3O nanoparticles. [GRAPHICS] .

Flexible ultracapacitor device fabricated with an organic electrode material- naphthalene diimide nitrile/reduced graphene oxide - Deshmukh, Ashvini B.; Biradar, Madan R.; Pawar, Meenakshi D.; Bhosale, Sidhanath V.; Shelke, Manjusha V. (Journal of Energy Storage, 2022)
In this work, we have demonstrated a high-performance flexible supercapacitor electrode based on reduced graphene oxide (rGO) and naphthalene diimide nitrile (NDI-CN) composite. The rGO/NDI-CN composite was prepared by a simple approach. This composite was well characterized using various techniques such as scanning electron microscopy (SEM), transmission electron microscopy (TEM) and X-ray photoelectron spectroscopy (XPS) etc. Besides, the pi -pi stacking of NDI-CN on rGO surface was confirmed using UV-vis and FTIR techniques. As fabricated rGO/NDI-CN composite was examined as an electrode material for the supercapacitor applications. The rGO/NDI-CN electrode has delivered an excellent specific capacitance (C-sp) of 336 F g(-1) at 0.5 A g(-1)current density. The fabricated supercapacitor (SC) displays robustness with 80 % capacitance retention over 10,000 cycles at higher current density of 10 A g(-1). To further explore the real-world application of electrode materials, the corresponding flexible supercapacitor was designed and examined. The flexible device exhibited an energy density of 9.54 mu Wh cm(-2) at a power density of 0.3 mWcm(-2). These results confirmed that the rGO/NDI-CN electrode material has good potential as an energy storage device. Furthermore, the facile construction and fabrication of flexible device displayed operation of LED when fully charged. The assembled flexible supercapacitor device could be bent and twisted, signifying the potential to be used in practical applications in various high-performance electrochemical devices.
Keywords: flexible supercapacitor; Naphthalene diimide; Organic molecule electrodes; pi -pi interaction; rGO

Ti3C2Tx-Nb2Mo3O14 composite as novel anode to realize high power density combined with high stability in a hybrid lithium-ion capacitor - Pawar, Meenakshi D.; Thripuranthaka, Marulasiddappa; Patrike, Apurva; Deshmukh, Ashvini B.; Chaturvedi, Vikash; Krishnan, Arun; Shivade, Rajkiran; Shelke, Manjusha V. (Energy Technology, 2023)
Lithium-ion capacitors (LICs), with their higher energy density at high power capability, stand out as the future generation of energy-storage devices. Herein, the nanocomposite of Ti3C2Tx MXene with Nb2Mo3O14 is prepared by a one-step hydrothermal method and studied as an electrode material for LIC. The asfabricated composite MXene niobium molybdenum oxide (MXNMO) achieves a high reversible capacity of 205 mAh g(-1) at 100 mA g(-1) current density with outstanding cyclability. Further, asymmetric LIC full-cell device composed of MXNMO anode with supercapacitor grade activated carbon as a cathode delivers an energy density of 37.8 Wh kg(-1) (0.25 A g(-1)) and a higher power density of 4244 W kg(-1) (5 A g(-1)) along with the excellent durability showing 85% capacitance retention over 4000 cycles at 0.5 A g(-1).
Keywords: lithium-ion capacitors; MXene; niobium molybdenum oxides; pseudocapacitive anode materials